Improving Emergency Department Services in Libyan Hospitals by Using Lean Six-Sigma "A Case Study" - Mohsen Isa; Malak Abderrazak (African Journal of Advanced Pure and Applied Sciences, 2025)
The use of Lean Six-Sigma methodology has spread in the development and improvement of health services in the developed and developing world. Previous studies have shown a great success in the improvements of various health services provided to patients using Lean Six-Sigma methodology. Therefore, the Libyan health facilities, especially emergency departments should take advantages of the use of this methodology and benefit from the experiences of countries that preceded us in the use of this methodology. This study aims to improve health services in emergency departments in Libyan hospitals using Lean Six-Sigma methodology. By designing, distributing and analyzing a questionnaire at the level of the state of Libya by taking samples to conduct this study represented in a number of hospitals in the city of Tripoli, and considering the Central Hospital in Tripoli as a case study, this research studies and analyses the problems and difficulties facing emergency departments, in order to identify the most important problems facing physicians and patients within different emergency departments using the Lean Six-Sigma methodology. The results of this research indicate that a range of issues faced by patients and physicians within the emergency departments have been identified. By analyzing the Pareto chart, thirteen of the most important issues were identified and prioritized. Through a cause-and-effect diagram, six main reasons for the long waiting time in the EDs were identified. A new process map was created where unnecessary movements and non-value-added activities were eliminated. A new Value Stream Map (VSM) was created where the average total time for the patient staying in the emergency department was reduced from 325 to 99 minutes if improvements are implemented.